School Experiences that Make an Impression – A Study on How to Promote Bildung and the Desire to Learn. Issue 7 (10th November 2021) - Ulvik, Marit; Kvam, Edel Karin; Eide, Liv
ABSTRACT: This qualitative study investigates, through focus groups, how students in upper secondary school in Norway experience schooling. The background for the study is a tension between measurable outcomes and the educational aim of supporting students' human growth, their Bildung . As teacher educators, we wanted to learn about situations that made an impression on students and thereby might promote Bildung and the desire to learn. Findings show that what made an impression was primarily related to teachers, fellow students, school atmosphere, and to aesthetic experiences and variations. Students emphasise teachers' attitudes, interpersonal skills and ability to vary their teaching. Teachers content knowledge was taken for granted. Based on the findings, we suggest implications for how to educate teachers, for teachers working conditions and for cooperation in schools. In order to promote students' Bildung, also teachers' human development needs to be put on the agenda.